THE ANALYSIS OF THE INFLUENCE OF GOLD PRICE, MARGIN, INFLATION, AND DOLLAR EXCHANGE RATES ON GOLD MURABAHAH FINANCING IN INDONESIAN SHARIA BANKING DURING THE PERIOD OF APRIL 2015-AUGUST 2019 - Ilyas Chaidir Rahmansyah; Lina Nugraha Rani (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This research employed a quantitative approach to investigate the relationship between dependent and independent variables and to test the hypotheses. The data utilized in this research were secondary data from the official website of Bank Indonesia (BI), the Financial Services Authority (OJK), the Central Statistics Agency (BPS), gold price providers in Indonesia, and monthly BUS & UUS bank statements in Indonesia. The population in this study consisted of 14 BUS and 20 UUS which registered on the Financial Services Authority. This research used a sampling technique using predetermined criteria so that a sample of 4 BUS and 1 UUS were obtained from April 2015 to August 2019. Moreover, the analysis technique employed in this research was panel data regression with EViews 9 statistical tools. The results of this research describe that the price of gold, inflation and the exchange rate of the dollar do not have a significant impact on the financing of Murabahah Gold, but margin have a significant impact and negative correlated with Murabahah Gold in Islamic banking in Indonesia, especially among Islamic Commercial Banks and Sharia Business Units.Keywords: Gold Prices, Inflation, Dollar Exchange, Murabahah Gold, Islamic BankingREFFERENCE Arumdati, Dewi. (2011). Cara kaya dengan investasi emas: Panduan cerdas berkebun emas. Yogyakarta: Araska PublisherAyub, M. (2007). Understanding Islamic finance. Jakarta: Gramedia Pustaka Utama.Anshori, Muslich & Sri Iswati. (2009). Metodologi penelitian kuantitatif. Surabaya: Airlangga University Press (AUP).Aye, G, Hector Carcel, Luis A. Gil-Alana, Rangan Gupta. (2017). Does gold act as a hedge against inflation in the UK? Evidence from a fractional cointegration approach over 1257-2016. Resources Policy, 54, 53-57.Balassa, B. (1990). The Effects of interest rates on savings in developing countries. Banca Nazionale del Lavoro Quarterly Review, 172, 101–18.Cai, J., Y.-L. Cheung and M. Wong. (2001). What moves the gold market?. Journal of Futures Markets, 21(3), 257–78.Clements, K., Renee, F. (2008). Commodity currencies and currency commodities. Resources Policy, 33, 55–73.Dewan Syariah Nasional Fatwa No.04/DSN-MUI/IV/2000 tentang Murabahah.Dierinck, B. (2012). Determinants of the gold price. Universiteit Gent, Faculteit Economie en Bedrijfskunde, Academiejaar 2011-2012Fabozzi, Frank, J & Franco Modigliani. (1996). Capital market. Second Edition New Jersey: Prentice Hall inc.Gaffen, D., Slater, J. (2009). Dollar, gold are suddenly inseparable. Abreast of the Market Column. Wall Street Journal, C1–C2.Ghazali, M. (2015). Sharia compliant gold investment in Malaysia: Hedge or safe haven?. Pacific-Basin Finance Journal, 34, 192-204.Gulseven, O. (2016). The Turkish appetite for gold: An Islamic explanation. Resources Policy, 48, 41-49Gujarati, Damodar N. (2006). Ekonometrika dasar. Jakarta: Penerbit Erlangga.Haugom, H. N. (1991). The Supply and Demand for Gold. Ph.D. dissertation. Simon Fraser University.Hsiao, C. (2003). Analysis of panel data. Second Edition. Cambridge: Cambridge University Press.Ismal, R. (2014). Assessing the gold murabahah in Islamic banking. International Journal of Commerce and Management, 24(4), 367-382.Kaufmann, Thomas D. and Richard A. Winters. (1989). The Price of gold: A simple model. Resources Policy, 15(4), 309-313.Ketentuan Pembiayaan Murabahah dalam praktek Syariah di Indonesia dijelaskan dalam Fatwa Dewan Syariah Nasional No. 04/DSN-MUI/IV/2000 tentang MurabahahLin, F. (2015). Does the value matter with the price of oil and gold? A dynamic analysis from time-frequency space. International review of economic and finance, 43, 59-71.Levin, E. & Robert E. Wright. (2006). Short-run and Long-run Determinants of the Price of Gold. World Gold Council, Research Study No. 32.Mahdavi, S. and Su Zhou. (1997). Gold and commodity prices as leading indicators of inflation: Tests of long-run relationship and predictive performance. Journal of Economics and Business, 49(5), 475-489Nugroho, Adi. (2005). Faktor-faktor Yang mempengaruhi margin pembiayaan murabahah (studi kasus pada PT. Bank Muamalat Indonesia). Skripsi tidak diterbitkan. Depok: Universitas Indonesia.Rao, B. S. and K. Nagabhushanam. (1960). India’s demand for import of non-monetary gold, non-monetary silver and merchandise, 1901–1913. Indian Economics Journal, 48(3), 34–38.Shafiee, S. and Topal, E. (2010). An overview of global gold market and gold price forecasting. Resources Policy, 35, 178-189.Suseno dan Siti Astiyah. (2009). Inflasi. Jakarta: Pusat Pendidikan dan Studi Kebanksentralan (PPSK) Bank Indonesia.Sugiyono. (2011). Metode penelitian kuantitatif, kualitatif dan R&D. Bandung: Afabeta.Starr, M. dan Ky Tran. (2008). Determinants of the physical demand for gold: Evidence from data panel. The World Economy.Susanti, R. (2017). Sejarah tranformasi uang dalam Islam. Jurnal of Islam and Plurality, Nomor 1.Pasal 19 Undang-Undang No.21 Tahun 2008 tentang Perbankan Syariah yang mengatur mengenai kegiatan usaha Bank Umum Syariah yang salah satunya adalah pembiayaan Murabahah.Pasal 1 ayat (13) Undang-Undang No.10 Tahun 1998 tentang Perbankan.PBI No.9/19/PBI/2007 jo. PBI No.10/16/PBI 2008 tentaang Pelaksanaan Prinsip Syariah dalam Kegiatan Penghimpunan Dana dan Penyaluran Dana serta Pelayanan Jasa Bank Syariah.Peraturan Bank Indonesia 10/16/PBI/2008 tentang perubahan terhadap Peraturan Bank Indonesia 9/19/PBI/2007 tentang penerapan prinsip syariah dalam penggalangan dana dan distribusi dana bank Syariah dan layanan tata kelolaPeraturan Bank Indonesia No.10/17/PBI/2008 tentang Produk bank Syariah dan Unit Usaha Syariah.Ranson David and H.C Wainwright. (2005). Gold and non-precious commodities as inflation hedges, Interest-Rate Outlook Research Summary, Wainwright Economics, November 2005.Widarjono, A. (2013). Ekonometrika: Pengantar dan aplikasinya. Jakarta: Ekonosia.Worthington, A. & M. Pahlavani. (2007). Gold investment as an inflationary hedge: cointegration evidence with allowance for endogenous structural breaks. Journal Applied Financial Economic Letters, 3(4), 259-262.